Patriarchal Discourse as Seen in Christina Dalcher’s Vox - Dyah Purwita Wardani; Intan Permatasari; Yanuaresti Wardhani (EQUALITY: Journal of Gender, Child, and Humanity Studies, 2024)
This study analyzes Christina Dalcher's Vox using the theory of representation by Stuart Hall 1997 and the discursive approach by Michel Foucault is an effective means of comprehending meaning through conversation. This theory analyzes patriarchal discourse experienced by female main characters. This study is categorized as qualitative research. This thesis has two kinds of data to support this research, primary and secondary. The primary data are collected from the dialogues and narration in Vox novel that represent the patriarchal system through the female characters. The secondary data are collected from various journals, books, and internet sources. In Vox novel, women always experience oppression and violence. It makes women’s lives miserable. The result of this study found four patriarchal discourse which cover patriarchal culture, patriarchal sexuality, patriarchal household production, and patriarchal state. Women experience psychological oppression carried out by President and Pure Movement. It begins with President and Pure Movement who control women’s life. This causes gender inequality which can give birth to subordination, marginalization, double burden, and violence. The last result is the ideological position of the author. The ideological position of the author does not support patriarchal system. Dalcher paints an original depiction of the current state of society by implying that women must be granted equal rights in society. Women have essentially the same rights as men, including the right to live an honorable life, to be free from fear, and to have the ability to choose their path in life.